Analisis Struktur dan Nilai Sosial dalam Antologi Puisi Menjadi Dongeng Karya Mukti Sutarman Espe - Habib Maulana Alby (Balai Bahasa Sumatera Utara, 2021)
The formulation of the problem discussed in this study analyzes the physical structure, inner structure, and social values in the poetry anthology Becoming a Fairy Tale. And the purpose of this research is to describe the structure of the poetry and social values in the poetry anthology, Becoming a Tale by Mukti Sutarman Espe. The research method used in examining the anthology of poetry to be fairy tales is descriptive qualitative method. The object of this research is the poetry collection book Becoming a Tale by Mukti Sutarman Espe, published by copyright prima archipelago and Pustaka KPK-Kudus Author’s Family, March 2019. The data analysis technique uses the semiotic model reading method, namely heristic and hermeneutic reading. The results of data analysis on the poetry anthology Becoming a Tale by Mukti Sutarman Espe can be concluded that the physical structure of poetry includes diction, images or images, concrete words, figure of speech, verification, and typography. And the inner structure is the theme, tone or atmosphere, and message. Meanwhile, the social values of poetry include care, loyalty, and kinship which are contained in the poetry anthology Becoming a Fairy Tale.